The optimal time for blood pressure measurement in end-stage renal failure patients on regular hemodialysis in Hospital University Sains Malaysia - Suardi, Kurnia Prima Sawai (2014)
Introduction: The appropriate time and method of blood pressure measurement in end stage renal failure (ESRF) patients on regular hemodialysis is still uncertain. During posthemodialysis, refilling of plasma volume from the interstitium took place. Therefore, the exact timing of when blood volume reaches equilibrates is uncertain. The inferior vena cava diameter normalizes when patient is euvolemic. Therefore, ultrasonographic direct measurement of inferior vena cava can be used to reflect the euvolemic state. Objectives: To determine the best time to measure post-hemodialysis blood pressure in ESRF patients on regular hemodialysis. To determine the variability of 24 hours blood pressure readings. Method: This is a cross sectional study involving 14 ESRF patients on regular hemodialysis in the HUSM outpatient hemodialysis unit. Hourly blood pressure reading was taken using ambulatory blood pressure monitoring device, starting from a day before hemodialysis session and 4 hours of post-hemodialysis, total duration of 24 hours. Upon completion of the hemodialysis treatment, serial ultrasonographic inferior vena cava diameter measurements were performed at 10, 30 and 60 minutes post-hemodialysis. Simultaneously, blood pressure readings were also taken at 10, 30 and 60 minutes posthemodialysis. Results were expressed as median (interquartile range) for data that was not normally distributed and described as mean (standard deviation) for normally distributed data. Repeated measure ANOVA was used to test for significance of blood pressure variability. Results: The inferior vena cava diameter was small at 10 minutes post-hemodialysis but it become normalize at 30 minutes and not much difference at 60 minutes. Blood pressure at 10, 30 and 60 minutes was found to be closer to average value at 60 minutes. Variability of the average blood pressure was not significant. Conclusions: The optimal time for blood pressure measurement in end stage renal failure patients on regular hemodialysis was found to be at 60 minutes post-hemodialysis based on euvolemic state reflected by IVC diameter. This study also found that there was no significant difference in blood pressure variability from one person to another. Keywords: end stage renal failure, hemodialysis, inferior vena cava diameter